Do Markets Overreact to Policy Signals? - Ni Putu Anindya Sarasija Prameswari; Nalarreason, Kadek Marlina; Andriadi , Komang Dandy (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This research looks into how the market responded to the Indonesia Stock Exchange's March 18, 2025, trading halt policy, which came after the IHSG fell by a precipitous 5.02%. The study compares aberrant return and trading volume activities before and after the incident, with a focus on LQ45 stocks. The study employs an event study methodology and analyzes 45 businesses listed on the LQ45. The assessment of market response is facilitated by the implementation of two distinct statistical methodologies: the Wilcoxon signed-rank test and the paired sample t-test. The results show no discernible variation in abnormal returns, indicating that the market had already factored in pertinent information when the uncertainty was halted. Trading volume activity, on the other hand, has significantly increased, suggesting that despite stable prices, investors acted in a certain way in response to the policy signal. According to the framework of signaling theory, these findings suggest that trading halts continue to affect market attitude and behavior even when price efficiency is preserved, acting as a communication tool as well as a technical intervention. This study advances our knowledge of how emerging markets interpret policy signals during times of increased uncertainty.